Student's Perceptions Towards Learning Arabic Language Through Digital Game - Wan Daud, Wan Ab Aziz; Ghani, Mohammad Taufiq Abdul; Zuhar, Nur Adnin Binti (Ijaz Arabi Journal of Arabic Learning, 2024)
In the current age of widespread digitization, technology has become an essential aspect of our everyday existence, significantly transforming how we gain knowledge and interact with our environment. This study aims to explore students' viewpoints on acquiring the Arabic language by employing digital games. This study used a qualitative methodology and performed semi-structured interviews with a purposively selected 30 college students. Their Arabic language program exposed These students to a digital game for five weeks. The findings revealed that students responded well to learning Arabic using digital games, consistently expressing their experiences in a unique and engaging educational environment. The post-implementation semi-structured interviews indicated that students recognized the integration of digital games as a valuable and advantageous approach, providing a distinct and captivating aspect to conventional learning methods. Hence, the results indicate that incorporating digital games into language teaching improves learning and benefits teachers and students in many courses that adopt this creative method.